Labour Supply after Inheritances and the Role of Expectations - Karina Doorley; Nico Pestel (Institute for the Study of Labor (IZA), 2016)
This paper examines the effect of wealth on labour market behaviour. Providing convincing evidence on this relationship is challenging since wealth and labour supply may be endogenously determined. We overcome this by looking at wealth shocks in the form of inheritances, distinguishing between unanticipated and anticipated inheritances. We provide a theoretical framework which outlines how an individual's labour market behaviour may be expected to react to a wealth shock under different circumstances including perfect/imperfect anticipation and a credit constrained environment. We test our model predictions using rich household and individual level micro-data for Germany. We find that women decrease their hours of work in response to an inheritance. Both men and women are more likely to stay self-employed after a large inheritance and male entrepreneurs are also more likely to recruit. The effect of inheritances on the self-employed is amplified for those who are credit constrained. The magnitude of these effects is similar for anticipated and unanticipated inheritances but the timing varies, with effects visible before the event in the case of anticipated inheritances.
Keywords: D31; J22; L26; 330; inheritance; wealth; labour supply; self-employment; Germany